Answer:
gₙ = gₙ₋₁ + 0.4, with g₁ = 6.4
Explanation:
The n-th term of an arithmetic sequence can be written as:
gₙ = g₁ + (n - 1)*d
Where g₁ is the first value, and d is the difference between any two consecutive terms of this sequence.
Then we have the equations:
g₅ = 8 = g₁ + (5 -1)*d
g₁₀ = 10 = g₁ + (10 - 1)*d
This is a system of equations, we can rewrite this as:
8 = g₁ + 4*d
10 = g₁ + 9*d
To solve this, the first step will be isolate one of the variables in one of the equations, i will isolate g₁ in the first equation:
g₁ = 8 - 4*d
Now we can replace this in the second equation to get:
10 = 8 - 4*d + 9*d
10 = 8 + 5*d
10 - 8 = 5*d
2 = 5*d
2/5 = d = 0.4
Now with this, we can find the value of g₁ by using the equation:
g1 = 8 - 4*d = 8 - 4*(2/5) = 8 - 8/5 = 6.4
Then the nth term of this sequence can be written as:
gₙ = 6.4 + (n - 1)*0.4
This relation also can be written as:
gₙ = gₙ₋₁ + d = gₙ₋₁ + 0.4, with g₁ = 6.4
Then the correct option is the second option.